After Standards : Engaging and Embedding History Standards Using International Best Practice to Inform Curriculum Renewal : Final Report. - Brawley, Sean; Clark, Jennifer; Dixon, Chris; Ford, Lisa; Nielsen, Erik; Ross, Shawn; Upton, Stuart (Office for Learning and Teaching, 2013)
History was a 'demonstration discipline' in the ALTC's Learning and Teaching Academic Standards project. While the new standards environment that TEQSA was earmarked to oversee has not yet materialised, this role presented the history discipline community with a unique opportunity to use TLOs developed through the LTAS project to drive cognate agendas around curriculum renewal. This is the final report from a project that built a community of practice through which Australian historians - systematically, universally, collegially, reflectively and effectively - responded to standards development and the resulting opportunities for curriculum renewal. The project was endorsed by the discipline's peak body (Australian Historical Association), the Australasian Council of the Deans of Arts, Humanities and Social Sciences, and had the active support of each of the 31 institutions that have history majors. This project modelled, demonstrated and evaluated approaches and processes in dissemination and implementation that will be applicable to other discipline communities.